Relationship of Physical Culture with Other Directions - Nurmatov Farkhat Abdualimovich (Research Parks Publishers, 2021)
Physically adequate development facilitated normal mental development. Chernyshevsky's views on the relationship of mental and physical processes of dialectical materialism to mental and physical activity are reflected in his works: